Thermotherapy in ’dwarf silver’ banana produced in the semi-arid region of Minas Gerais - Fernandes, Martielle Batista; Sousa, Irisléia Pereira Soares de; Matos, Amanda Dayanne Malta; Moura, Marielly Maria de Almeida; Castro, Sabrina Gonçalves Vieira de; Santos, Michelle de Oliveira; Almeida, Luciele Barboza de; Dias, Wlly Polliana Antunes; Mizobutsi, Gisele Polete; Mizobutsi, Edson Hiydu (Seven Editora, 2024)
Anthracnose stands out among the rots that can occur in the postharvest phase of bananas. The objective of this study was to evaluate thermotherapy in the control of anthracnose in ’Prata Anã’ banana produced in the North of Minas Gerais. Bananas of the Prata Anã variety were divided into bouquets of three fruits and inoculated with Colletotrichum musae. The bouquets were submitted to thermotherapy at five temperatures (40, 44, 48, 52 and 56 °C) for four immersion times (4, 8, 12 and 16 minutes) and control. The treatments were repeated five times in a completely randomized design. The area under the incidence progress curve (AACPI) and the area under the severity progress curve (AACPS) were calculated. To evaluate the efficiency of thermotherapy compared to chemical control, the fruits were submitted to the following treatments: thermotherapy with and without fungicide application and fruits treated only with fungicide, with the fruits without thermotherapy and without fungicide application being the control. After fifteen days of storage, the fruits were evaluated for anthracnose severity. The results of the experiments were submitted to analysis of variance and regression and the means were compared using the Scott-Knott test (p<0.05). The control was compared to the treatments using Dunnett’s test (p<0.05). The lowest AACPI values for anthracnose were observed at a temperature of 48 °C for 8 and 16 minutes. Thermotherapy at 52 °C after 8 minutes of immersion, in addition to reducing the AACPS of anthracnose in the fruits by up to 81.6%, delayed their maturation. The fruits submitted to thermotherapy at 56 °C showed greater disease severity and resulted in the advancement of their maturation. Thermotherapy reduces the severity of anthracnose in fruits in a similar way to the use of fungicide, but the association of both results in better control of the disease in ’Prata Anã’ banana. Thermotherapy is an efficient technique to reduce the severity of the disease in ’Prata Anã’ bananas produced in the north of Minas Gerais. DOI:https://doi.org/10.56238/sevened2024.007-015